The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0191164
|View full text |Cite
|
Sign up to set email alerts
|

Implicit learning deficit in children with Duchenne muscular dystrophy: Evidence for a cerebellar cognitive impairment?

Abstract: This study aimed at comparing implicit sequence learning in individuals affected by Duchenne Muscular Dystrophy without intellectual disability and age-matched typically developing children. A modified version of the Serial Reaction Time task was administered to 32 Duchenne children and 37 controls of comparable chronological age. The Duchenne group showed a reduced rate of implicit learning even if in the absence of global intellectual disability. This finding provides further evidence of the involvement of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 51 publications
0
19
0
5
Order By: Relevance
“…Saturation in the learning performance also indicates poor availability of neural resources to support higher level cognitive processing consistent with the neural integrity as suggested by Dixon et al 37 . The distal mutation location in DMD has previously been associated to severe intellectual deficits 5,19,35,38 . www.nature.com/scientificreports/ Poor performance in recalling list B indicates susceptibility to interference from previously acquired memory.…”
Section: Discussionmentioning
confidence: 99%
“…Saturation in the learning performance also indicates poor availability of neural resources to support higher level cognitive processing consistent with the neural integrity as suggested by Dixon et al 37 . The distal mutation location in DMD has previously been associated to severe intellectual deficits 5,19,35,38 . www.nature.com/scientificreports/ Poor performance in recalling list B indicates susceptibility to interference from previously acquired memory.…”
Section: Discussionmentioning
confidence: 99%
“…People with DMD mainly experience motor impairments (primarily muscle weakness), but a large number of people with DMD also experience cognitive impairments and impaired ability in processing visual information [28]. A recent study showed that even individuals with DMD without intellectual disability have a deficit in implicit learning [29]. Therefore, we cannot assume that individuals with DMD will also improve due to implicit learning that will lead to lower cognitive effort.…”
Section: Trainingmentioning
confidence: 99%
“…Le cervelet jouerait un rôle important dans la détection des séquences d'événements, ainsi que dans l'acquisition et l'automatisation de procédures cognitives. L'objectif de l'étude [1] est de comparer, à l'aide d'un test d'apprentissage implicite (Serial Reaction Time Task -SRTT, version modifiée), les capacités d'apprentissage implicite chez des enfants atteints de DMD sans retard intellectuel (n = 32) versus un groupe contrôle d'enfants se présentant avec un développement normal et appariés pour l'âge (n = 37). Le SRTT évalue l'apprentissage d'un rythme d'apparition d'un stimulus, sans que le sujet n'ait conscience de réaliser une tâche de mémoire.…”
Section: Claire-cécile Michon Christian Réveillèreunclassified